Preclinical Development and in Vivo Efficacy of Ceftiofur-Plga Microparticles - Constandil-Cordova, L; Vilos-Ortiz, C; Velasquez, L (Public Library of Science, 2015)
Drug delivery systems based on polymeric microparticles represent an interesting field of development for the treatment of several infectious diseases for humans and animals. In this work, we developed PLGA microparticles loaded with ceftiofur (PLGA-cef), a third-generation cephalosporin that is used exclusively used in animals. PLGA-cef was prepared by the double emulsion w/o/w method, and exhibited a diameter in the range of 1.5-2.2 μm, and a negative ζ potential in the range of -35 to -55 mV. The loading yield of PLGA-cef was ∼7% and encapsulation efficiency was approximately 40%. The pharmacokinetic study demonstrated a sustained release profile of ceftiofur for 20 days. PLGA-cef administrated in a single dose was more effective than ceftiofur non-encapsulated in rats challenged with S. Typhimurium. The in vivo toxicological evaluation showed that PLGA-cef did not affect the blood biochemical, hematological and hemostasis parameters. Overall, the PLGA-cef showed slow in vivo release profile, high antibacterial efficacy, and low toxicity. The results obtained supports the safe application of PLGA-cef as sustained release platform in the veterinary industry. © 2015 Vilos et al.